Community Awareness and Participation for Land and Forest Fire Prevention and Implementation of Lancang Kuning Nusantara System Application in Toba District, North Sumatra Province - A. Rampengan, Stevi; Herwanto, Herwanto; Rajagukguk, Jenni Ria; Suwanda, Suwanda (International Journal of Engineering, Science and Information Technology, 2024)
This study employs a sociometric analysis of Community Concern and Participation in Implementing the Lancang Kuning Nusantara Application for Forest and Land Fire Prevention in Toba Regency, Indonesia. With a sample of 401 respondents, the study aims to comprehensively understand social interactions and community engagement in this context. Results indicate that the perception score (X(i.1)) and participation score (X(i.2)) are high or significant, reflecting positive community awareness and active involvement in fire prevention activities. However, the acceptability score (X(i.3)) is low or insignificant, suggesting potential dissatisfaction or skepticism regarding the effectiveness or implementation of current programs. Furthermore, standard deviation analysis reveals that variability in respondent ratings is generally within control, with only 2 out of 15 testing points showing high standard deviation, while 13 are within acceptable limits. Nevertheless, the proportion of respondents who rate low (PRMR) exceeds the desired threshold of 10% across all variables, indicating that many respondents have low evaluations. These findings suggest a need for improved communication, education, and potential adjustments to enhance the acceptability and effectiveness of the fire prevention initiatives and the Lancang Kuning Nusantara System application.